History of Morgellons disease: from delusion to definition - Middelveen MJ; Fesler MC; Stricker RB (Dove Medical Press, 2018)
Marianne J Middelveen,1 Melissa C Fesler,2 Raphael B Stricker2 1Atkins Veterinary Services, Calgary, AB, Canada; 2Union Square Medical Associates, San Francisco, CA, USA Abstract: Morgellons disease (MD) is a skin condition characterized by the presence of multicolored filaments that lie under, are embedded in, or project from skin. Although the condition may have a longer history, disease matching the above description was first reported in the US in 2002. Since that time, the condition that we know as MD has become a polemic topic. Because individuals afflicted with the disease may have crawling or stinging sensations and sometimes believe they have an insect or parasite infestation, most medical practitioners consider MD a purely delusional disorder. Clinical studies supporting the hypothesis that MD is exclusively delusional in origin have considerable methodological flaws and often neglect the fact that mental disorders can result from underlying somatic illness. In contrast, rigorous experimental investigations show that this skin affliction results from a physiological response to the presence of an infectious agent. Recent studies from that point of view show an association between MD and spirochetal infection in humans, cattle, and dogs. These investigations have determined that the cutaneous filaments are not implanted textile fibers, but are composed of the cellular proteins keratin and collagen and result from overproduction of these filaments in response to spirochetal infection. Further studies of the genetics, pathogenesis, and treatment of MD are warranted. Keywords: Morgellons disease, dermopathy, Lyme disease, Borrelia burgdorferi, spirochetes